2020
DOI: 10.3389/fonc.2020.606574
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Fluorescein-Assisted Confocal Laser Endomicroscopy (CONVIVO® System) in Patients With Glioblastoma: Results From a Prospective Study

Abstract: BackgroundConfocal laser endomicroscopy (CLE) allowing intraoperative near real-time high-resolution cellular visualization is a promising method in neurosurgery. We prospectively tested the accuracy of a new-designed miniatured CLE (CONVIVO® system) in giving an intraoperative first-diagnosis during glioblastoma removal.MethodsBetween January and May 2018, 15 patients with newly diagnosed glioblastoma underwent fluorescein-guided surgery. Two biopsies from both tumor central core and margins were harvested, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…Alternatively, fluorescein could be combined with Raman spectroscopy, which has been shown to accurately delineate tumor versus normal brain at the margins of resection, with superior performance compared to 5-ALA (55). Confocal laser endomicroscopy has also been combined with fluorescein and recently investigated as a means of increasing extent of resection by providing real-time intraoperative verification of pathologic tumor tissue (56)(57)(58). Several studies have also mentioned the potential benefit of quantitatively measuring fluorescence intensity and integrating this technology with the operative microscope, which could increase both the safety and the sensitivity of fluorescein as an adjunct for glioma resection (9,17,29).…”
Section: Future Directionsmentioning
confidence: 99%
“…Alternatively, fluorescein could be combined with Raman spectroscopy, which has been shown to accurately delineate tumor versus normal brain at the margins of resection, with superior performance compared to 5-ALA (55). Confocal laser endomicroscopy has also been combined with fluorescein and recently investigated as a means of increasing extent of resection by providing real-time intraoperative verification of pathologic tumor tissue (56)(57)(58). Several studies have also mentioned the potential benefit of quantitatively measuring fluorescence intensity and integrating this technology with the operative microscope, which could increase both the safety and the sensitivity of fluorescein as an adjunct for glioma resection (9,17,29).…”
Section: Future Directionsmentioning
confidence: 99%
“…The last available work to date concerning ex vivo imaging in brain tumors surgery was the work of our group in 2020. We prospectively studied ex vivo the ability of Convivo to confer an intraoperative first-diagnosis during GBM removal, by blindly comparing intraoperative CLE and frozen/permanent sections results at both central core and tumor margins of tumors [ 42 ]. We were interested in both identifying the ability of such system in offering an intraoperative diagnosis, along with the ability to categorize morphological patterns, such as cellularity, vascularization and necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the work of Belykh in 2020 should be considered as a miliary stone, due to the extremely rigorous blinded study in analyzing CLE images from both neuropathologist and experienced/unexperienced neurosurgeons’ points of view and the huge amount of tumors investigated [ 41 ]. Looking at our work, in 2020 we reported the results of a rigorous blinded and prospective study where an optimal diagnostic concordance was obtained at the central core of 15 HGGs analyzed [ 42 ]. Even though one of the major limits of this study was the fact that just one hystotipe of tumor was analyzed, hence rendering it unsuitable to study the differential diagnosis ability of Convivo (programmed for the next in vivo study), we reported an optimal concordance among CLE imaging and histopathological/frozen section analysis at the central core of the different cases, with a rigorous blinded design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of the observed changes in optical properties are of relevant nature, especially if these fluorescent-based assays are used for further diagnostic purposes. Furthermore, in the clinical setting, the utilization of NaFl in combination with in-depth in vivo and ex vivo imaging techniques such as confocal laser endomicroscopy has also been discussed in recent studies in aiding histopathological diagnoses ( 25 , 26 ). Hence, the increasing role of NaFl in such settings poses increasing interest on NaFl tumor kinetics, and further analysis of its spectroscopic features may help to distinguish its free form from fluorescein metabolites (fluorescein glucuronide).…”
Section: Discussionmentioning
confidence: 99%